Avaliacąõ da Concepcąõ Ambiental em Alunos do 3Ano do Ensino Médio: Um estudo de caso em Bauru/SP - Cardoso, Christopher De Andrade; Silverio, Giovana Henrique; Guijarro, Maria Elza Campos; Antoniassi, Beatriz [UNESP]; Siqueira, Marcos Vinícius Bohrer Monteiro (Fronteiras: Journal of Social, Technological and Environmental Science, 2017)
Although environmental themes are widely discussed in schools, many concepts related to this theme are unknown or poorly understood by teachers and students. This article presents the data obtained through a structured questionnaire whose objective was to evaluate the knowledge of 193 students of the 3rd year of secondary education in the city of Bauru/SP, both public and private schools. After answering the questionnaire, which addressed topics related to ecology, environmental education, genetics and deforestation/reforestation, two pedagogical interventions were proposed to the students through which a review of the concepts required in the questionnaire was carried out. The first and second applications were 45.5% and 56.1% (public) and 57.9% and 67.8% (private), respectively. The groups presented a statistically significant difference (p 0.05) from the comparison of the means of correct answers. It was observed that the students do not know many of the concepts presented in the interventions.
Environmental conception evaluation in 3rd year of high school students: A case study in Bauru/SP
Keywords: Environmental Education; Structured Questionnaire; Teaching of Biology